COPD patients need more information about self-management: a cross-sectional study in Swedish primary care - Hanna Sandelowsky; Ingvar Krakau; Sonja Modin; Björn Ställberg; Anna Nager (Taylor & Francis Group, 2019)
Objective: In Sweden, patients with chronic conditions, such as chronic obstructive pulmonary disease (COPD), often receive education at specialized nurse-led clinics at primary health care centers (PHCCs). Identifying patients' needs for information about COPD is the key to individualized care. This study aimed to assess self-reported needs for information about COPD in primary care patients with either moderate (GOLD 2) or severe (GOLD 3) COPD and identify patient characteristics and exacerbation patterns associated with the findings. Design: A cross-sectional study. Setting: Twenty-four PHCCs in Stockholm, Sweden. Subjects: Randomly selected primary care patients with COPD in GOLD stages 2 and 3 (n = 542). Main outcome measures: The Lung Information Needs Questionnaire (LINQ) was used to assess perceived information needs. Spirometry results and descriptive, self-reported data on patient factors such as exacerbation history, treatment, smoking, weight/height, comorbidities, health care contacts, education and symptoms were collected. Results: Overall, the greatest reported needs were for information about self-management and diet. GOLD 2 patients (68%) expressed greater needs for information than GOLD 3 patients (32%). We found significant associations between high information needs and patient-related factors such as 'No assigned GP' (OR = 4.32 [95% CI 2.65-7.05]) and 'No contact with COPD nurse in the past 12 months' (OR = 1.83 [95% CI 1.19-2.81]). Conclusion: COPD patients felt they knew too little about self-management of their disease. Low information needs were strongly associated with continuity in patient-GP consultations and moderately associated with contact with a COPD nurse. These associations were strongest in patients with moderate COPD. Key points: As patients with COPD often have multimorbidity, identifying patients' needs for information about COPD is essential to providing individualized patient education and care. In this study of 542 patients from 24 Swedish primary care centers, we found that:Patients with COPD, particularly those with moderate airflow limitation (i.e. GOLD 2) felt they needed more information about COPD than currently provided by health care professionals in primary care. Low information needs were strongly associated with continuity in patient-GP consultations and moderately associated with contact with a COPD nurse. GPs' part in COPD patient education should not be overlooked, as individualized COPD care relies on GPs' expertise in managing patients with multimorbidity.